A new species of Pseudosesarma Serène & Soh, 1970 (Crustacea: Brachyura: Sesarmidae) from Cochin in southwestern India - Ng, Peter K. L.; Rani, Varghese; Nandan, S. Bijoy (Zootaxa, 2017)
A new species of mangrove sesarmid crab of the genus Pseudosesarma Serène & Soh, 1970, is described from Cochin, southwest India. The species superficially resembles P. edwardsii (De Man, 1887), known from Myanmar and many parts of India; the proportions of the carapace and male pleon also ally it with P. crassimanum (De Man, 1887) from Myanmar, Sri Lanka and Southeast Asia. Pseudosesarma glabrum n. sp., however, is easily separated from P. edwardsii and P. crassimanum primarily by the almost glabrous dorsal surface of the carapace and the distinctive form of its male first gonopod.